Peace Communication in Cross-border Media Flows. (26th April 2018) - Kumar, Anup; Semetko, Holli A
Abstract: Peace communication in media flows fosters civil discourse, emphasizes shared culture, values, collective well-being, and works for reduction in violence and conflict. This study addresses a gap in the literature on citizen-initiated peace communication in the context of interstate relations, conflict and public diplomacy, with a focus on the understudied case of media flows between India and Pakistan, two nuclear-armed nations embroiled in perpetual enmity since the 1947 Partition. Revolutions in ICTs led to a shift in the dominant media flow from top-down and statist to bottom-up, with horizontal media flows fostered by individuals and groups now on social media platforms that opened up space for civil discourse. Dozens of different online citizen groups promoting peace on Facebook, YouTube and other platforms lead to the conclusion that peace communication in cross-border media flows indeed may have the potential to result in peace dividends in the form of fostering civil communication in shared values, culture, and collective well-being.